Pengungkapan Efektivitas Model Pembelajaran Melalui Anava Dua Faktorial - Arigiyati, Tri Astuti; Istiqomah, Istiqomah (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2018)
This study aims to determine the effectiveness of the learning model that is influenced by the level of students' initial abilities and the combined influence (interaction effect) between the learning model and the students' initial level of ability to the students' mathematics learning outcomes. The learning model has a central function in learning, namely as a tool and a way to achieve learning goals. The type of research used in this study is quasi-experimental. The research subjects used as the subject of the trial were Yogyakarta State and Private Middle School Students. The object of this research is the students' initial abilities and learning outcomes of mathematics by using Write and Conventional Think Talk learning models. Data collection techniques used are test techniques and documentation techniques. Data were analyzed by two factors, both for initial ability test scores and learning outcome test scores and post anava test using Scheffe Test. The results of the study with Î± = 5% indicate: 1) The Think Talk Write learning model is more effective than the conventional learning model. (2) Learning outcomes of high-skilled students are better than students who have moderate and low initial abilities, and (3) there is no interaction between learning methods and students' initial level of ability based on learning outcomesKeywords: Effectiveness, Think Talk Write, AnavaAbstractThis study aims to determine the effectiveness of the learning model that is influenced by the level of students' initial abilities and the combined influence (interaction effect) between the learning model and the students' initial level of ability to the students' mathematics learning outcomes. The learning model has a central function in learning, namely as a tool and a way to achieve learning goals. The type of research used in this study is a quasi-experimental. The research subjects used as the subject of the trial were Yogyakarta State and Private Middle School Students. The object of this research is the students' initial abilities and learning outcomes of mathematics by using Write and Conventional Think Talk learning models. Data collection techniques used are test techniques and documentation techniques. Data were analyzed by two factors, both for initial ability test scores and learning outcome test scores and post anava test using Scheffe Test. The results of the study with Î± = 5% indicate: 1) The Think Talk Write learning model is more effective than the conventional learning model. (2) Learning outcomes of high-skilled students are better than students who have moderate and low initial abilities, and (3) there is no interaction between learning methods and students' initial level of ability based on learning outcomes.Â Keywords: Effectiveness, Think Talk Write, Anava